Development of Prototype Scheduling and Sequencing Software for Job Shop Manufacturing in Sheet Metal Fabrication - Mohamed Rasin, Mohamad Zaihirain (2002)
A software program has been developed to ease the process of scheduling and sequencing number of jobs to certain number of machines for job shop manufacturing in sheet metal fabrication. The program is designed based on the present operation at Technology Park Malaysia (TPM) - Production Engineering using available priority dispatching rules and multiple performance measures. For n by m job shop scheduling problems, where n is the number of jobs and m is the number machines, there are (n!)m possible schedules. In a typical job shop, hundreds of scheduling decisions must be made daily. Scheduling process, which is to organise, maintain, update and reschedule the job, is very tedious work and time consuming. For five jobs passing through one machine, there are 120 time charts just to show all possible sequence patterns. To plot the charts manually is not. a practical solution and ridiculous. Identifying the performance measures to be used in selecting the schedule is important. The schedule should reflect managerially acceptable performance measures. A logical strategy is thus to pursue methods that can consistently generate good schedules with quantifiable quality in a computationally efficient manner.